Demographic growth and its relationship with economic growth in Algeria - oucif, mohamed (Journal of Social Sciences and Humanities, 2016)
This study aims to examine the relationship between the demographic growth rate and the economic growth rate in Algeria. The first rate represents the indicator or reflection of population size and dynamics in any country, while the second represents that country’s economic performance. Most studies have shown that the relationship between these two variables is reciprocal, as each one influences and is influenced by the other, depending on the specific characteristics of each country. By examining the quantitative evolution of Algeria’s population through the study of demographic phenomena affecting it over a considerable period of time, this research employs appropriate statistical tools and techniques for such studies, including tables and statistical curves. To assess the degree of the potential relationship between demographic growth and economic growth in Algeria—which is considered a special case at all levels, according to many specialists—this study takes into account the country’s vast territorial area, its renewable and non-renewable natural resources, and its important human resource base, mainly composed of youth. Despite these advantages, Algeria has not yet achieved the objectives set in previous decades for its economic and social development.